2007
DOI: 10.1523/jneurosci.2085-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dominant-Negative Inhibition of M-Like Potassium Conductances in Hair Cells of the Mouse Inner Ear

Abstract: Sensory hair cells of the inner ear express multiple physiologically defined conductances, including mechanotransduction, Ca 2ϩ , Na ϩ , and several distinct K ϩ conductances, all of which are critical for normal hearing and balance function. Yet, the molecular underpinnings and their specific contributions to sensory signaling in the inner ear remain obscure. We sought to identify hair-cell conductances mediated by KCNQ4, which, when mutated, causes the dominant progressive hearing loss DFNA2. We used the dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 41 publications
(87 reference statements)
3
58
0
Order By: Relevance
“…Previous studies have suggested that in the inner ear the K v 7.4 channel is highly expressed in IHC and outer hair cells (4). Because K v 7 channel-mediated currents are activated at low membrane voltages, it has been suggested and demonstrated that K v 7.4 currents contribute substantially in establishing V rest of IHCs and, in so doing, control intracellular Ca 2ϩ concentrations (15,16). Although not demonstrated either in vitro or in vivo, the implications of these findings are that a pathological rise in intracellular Ca 2ϩ may ensue due to reduced expression or dysfunction of K v 7.4 in DFNA2, leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that in the inner ear the K v 7.4 channel is highly expressed in IHC and outer hair cells (4). Because K v 7 channel-mediated currents are activated at low membrane voltages, it has been suggested and demonstrated that K v 7.4 currents contribute substantially in establishing V rest of IHCs and, in so doing, control intracellular Ca 2ϩ concentrations (15,16). Although not demonstrated either in vitro or in vivo, the implications of these findings are that a pathological rise in intracellular Ca 2ϩ may ensue due to reduced expression or dysfunction of K v 7.4 in DFNA2, leading to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, determination of the properties of native K v 7 channels may be obscured by regulation of KCNE subunits (41) and the ␣-subunit interaction with K v 10.1 (ERG1) (42)(43)(44). Thus, null deletion of one subtype of K v 7 channels may produce a modest phenotype (39), but a dominant negative version of a K v 7.4 channel subunit will impair the entire K ϩ channel class, resulting in a profound auditory phenotype (16,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I K,L confers more hyperpolarized resting potentials to type I hair cells. However, Holt et al (2007) concluded that loss of I K,L in type I hair cells did not depolarize the cells' resting potential to the extent expected, because in the absence of I K,L , persistent I K1 may compensate. Figure 1, B and D, shows mean steady-state I(V) curves from type II cells at the same ages shown in Fig.…”
Section: Inward Rectifier Currents In Utricle Hair Cellsmentioning
confidence: 95%
“…The M-channel has been implicated also in the neurogenesis of tinnitus (Holt et al, 2007). In the current study the EC 50 of linopirdine was 176 μM, which is approaching a physiological range and may thus serve as an adjunctive therapy for tinnitus, but would have to be made available once again to the consumer market.…”
Section: Discussionmentioning
confidence: 69%